Efficacy of ketamine gargle 40 mg and benzydamine HCl 0.075% in reducing post intubation sore throat - Eko Bambang Subekti MuhdarAbubakar Djayanti Sari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Sore throat is a frequent complication in postoperative patients under general anesthesia whichis performed with endotracheal tube intubation. This effect occurs because of mucosal irritationand damage and airways inflammation due to a lubricant gel on laryngoscopy or an emphasis ofendotracheal tube cuff. This study was conducted to compare the efficacy of ketamine 40 mggargle with benzydamine HCl 0.075% gargle in reducing post intubation of sore throat prior tothe insertion of endotracheal tube. A prospective randomized double blind controlled clinicaltrial enrolled patients aged 18-50 years with physical status of ASA I and II whounderwent elective surgery with general anesthesia in Dr. Sardjito General Hospital, Yogyakarta.Subjects were divided into 2 groups. 50 patients of group A were given 30 mL ketamine gargle40 mg and 51 patients of group B were given 30mL benzydamine HCl gargle 0.075%. The sorethroat was measured whenever the patients were fully awake, 2 hours and 4 hours post-extubationwith Canbay score (no pain, mild pain, moderate pain and severe pain). There was a significantdifference (p<0.01) in sore throat incidence of both groups especially at fully awake and 2hours post-extubation; 20% in group A versus 66.7% in group B at fully awake and 16% ingroup A versus 58,8% in group B at 2 hours of post-extubation. However, there was not anysignificant difference in sore throat incidence of both groups at 4 hours post-extubation(p=0.394). In conclusion, giving ketamine gargle 40 mg 5 minutes before intubation is moreefficient in reducing sore throat after endotracheal tube-general anesthesia compared withbenzydamine HCl 0.075% at fully awake and 2 hours post-extubation.Keywords : endotracheal tube - sore throat - ketamine gargle - benzydamine HCl gargle